PUBLIC - PRIVATE PARTNERSHIP AS AN ENCOURAGEMENT TOOL OF INNOVATIVE DEVELOPMENT - Tkacheva, Tatyana; Afanasjeva, Lyubov Viktorovna (Journal of Applied Engineering Science, 2017)
The main aim of this study is to substantiate the assumption that public-private partnership should be considered as an encouragement tool of innovative development. We use theoretical and empirical methods of research and a review of PPP impact on innovative development of state (region). It is shown that economic infrastructure (e.g., transport) is usually a priority for PPPs than social infrastructure is. We examine the mechanism of public-private partnership to improve the efficiency of budget expenditures. It is proved that at each stage of PPP development the emphasis has consistently shifted to those areas which were a "breakthrough" to solve economic and social problems of the state and to improve competitiveness and ensure economic security of the state at the time.